Explore the extended impacts on psychological well-being in older adults through application of virtual reality technology: An integrative review - Irene Yuen Fung Wong; Leona Yuen Ling Leung (International Journal of Nursing Studies Advances)
Background: The application of virtual reality technology is often presented as an emergent method to reduce older adults’ mental problems however the results of evaluations remain inconsistent. There has been little exploration of the extended impacts of virtual reality technology on older adults’ psychological well-being and, in particular, on their underlying psychological demands. Objectives: This study aims to conduct an integrative review of recent literature to explore the extended impacts on the psychological well-being in older adults through application of virtual reality technology. Design: This study adopted Whittemore and Knafl’s integrative review methodology. Methods: Four major databases including Cumulative Index to Nursing and Allied Health Literature (CINAHL) Complete, Medical Literature Analysis and Retrieval System Online (MEDLINE), ProQuest, and Web of Science were searched. The included studies were in full text, peer reviewed, English written, published from January 2020 to October 2024, involved a primary experimental virtual reality-based intervention for older adults aged 60 or above, and reported at least one or more psychological well-being impacts. Among the 13 included literature, 6 were randomized controlled trial studies and 7 were quasi-experimental studies, of which, 8 used quantitative design, 2 used qualitative design and 3 used mixed-methods research design. A total of 952 participants were involved. The research settings included nursing homes/elderly care facilities, university aging centre, medical centre, and designated research site. Critical Appraisal Skills Programme (CASP) Checklists were adapted and employed to appraise the study quality. Ryff’s framework of Psychological Well-Being was used as the underpinning idea. Results: Among the 13 articles, 46% (n=6) were published in 2023 and 2024. The included studies were conducted in diverse geographical locations including the Middle East (n=2, 15.4%), Asia (n=5, 38.5%), Europe (n=4, 30.8%), North America (n=1, 7.7%), and Australia (n=1, 7.7%). The virtual reality interventions included reminiscence activities, recreation gaming, entertainment and relaxation experiences, therapeutic exercise, social virtual platforms and combined therapy intervention. Five extended impacts were identified finally. Conclusions: Through this review, we highlight nurse professionals should take note of the extended impacts and the fulfilment on older adults’ underlying psychological demands through application of virtual reality technology.